Schizandrin protects H9c2 cells against lipopolysaccharide‐induced injury by downregulating Smad3. Issue 5 (22nd February 2019) - Zhang, Xuehua; Zhao, Yanyan; Bai, Dong; Yuan, Xiutai; Cong, Shan
Abstract: Schizandrin is a major bioactive constituent of Schisandra chinensis (Turcz.) Baill with antioxidant and anti‐inflammatory properties. The objective of this study was to explore the potential effects of schizandrin on a cell model of myocarditis. The H9c2 cells were treated with schizandrin alone or in combination with lipopolysaccharide (LPS), after which, cell survival, migration, and the release of inflammatory cytokines were assessed. Moreover, downstream effectors and signaling pathways were studied to reveal the possible underlying mechanism. As a result, LPS stimulation induced significant cell damage as cell viability was repressed and the apoptosis was induced. In the meantime, LPS promoted the release of proinflammatory cytokines including interleukin 1β (IL‐1β), IL‐8, IL‐6, and tumor necrosis factor (TNF‐α) while repressing the release of the anti‐inflammatory cytokine IL‐10. Schizandrin could promote H9c2 cell migration and long‐term treatment (7 days) enhanced cell viability. More interestingly, pretreatment with schizandrin attenuated LPS‐induced cell loss and inflammatory response. Besides this, Smad3 was a downstream effector of schizandrin. The beneficial effects of schizandrin on the H9c2 cells were attenuated when Smad3 was overexpressed. Moreover, the silencing of Smad3 deactivated c‐Jun N‐terminal kinase (JNK) and nuclear factor κB (NF‐κB) pathways. This study preliminarily demonstrated that schizandrin prevented LPS‐induced injury in the H9c2 cells and promoted the recovery of myocardial tissues by enhancing cell viability and migration. Schizandrin conferred its beneficial effects possibly by downregulating Smad3 and inhibiting the activation of JNK and NF‐κB pathways.